General System Theory: the Biotic Systems, Basic Concepts, Laws of Functioning - T. L. Botasheva; A. V. Chernositov; O. P. Zavodnov; E. B. Gudz (Медицинский вестник Юга России, 2011)
This article presents a short review of historical background for the creation of the general theory of systems. There are also given basic statements of this theory and as well her scientific significance in the field of scientific facts’ synthesis is shown. The greatest emphasis is placed on biotic systems. There are presented the questions of structure, function and evolution in medical and biological aspects.